Moldova : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper reviews economic developments in the Republic of Moldova during 1993-97. In 1993, the authorities adopted a comprehensive program of financial stabilization supported by a stand-by arrangement with the IMF. By 1995, the fiscal deficit had been cut to 5 3/4 percent of GDP and annual inflation had fallen to 24 percent. Exports and imports recovered rapidly, with the current account deficit narrowing to 8 1\2 percent of GDP. In 1996, the authorities adopted a three-year program supported by resources under the extended IMF facility to accelerate and deepen the structural reforms.